Social Media Influencers and Purchase Intention: The Role of Parasocial Relationships on TikTok - Renasabylla Putri Asriliorentika; Ratih Amelia (Target : Jurnal Manajemen Bisnis, 2026)
The rapid growth of Indonesia’s beauty industry and TikTok’s dominance as a digital marketing platform present both opportunities and challenges for brands seeking to understand how consumer behavior is influenced by influencers. Although the role of social media influencers in driving purchase intent has been extensively studied, the psychological mechanisms linking the two through parasocial relationships remain underexplored on the TikTok platform in Indonesia. This study aims to analyze the influence of social media influencers on the intention to purchase beauty products, with parasocial relationships serving as a mediating variable among followers of the TikTok account @catlovers29 in Surabaya. A quantitative approach using an associative survey method was employed. Data were col- lected via an online questionnaire, and after undergoing purposive sampling and data screening, 192 valid respondents were obtained and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS version 4. The results show that social media influencers have a positive and significant effect on both purchase intention and parasocial relationships, and that parasocial relation- ships, in turn, have a positive and significant effect on purchase intention. Parasocial relationships were found to partially mediate the effect of social media influencers on purchase intention. These findings imply that the emotional bond formed between followers and influencers plays a more dominant role in driving interest in purchasing beauty products than content quality alone does; therefore, beauty brands need to prioritize selecting influencers capable of building strong parasocial bonds with their follower communities.